Explaining variation in cassava root yield response to fertiliser under smallholder farming conditions using digital soil maps - Masunga, R. H.; Chernet, M.; Ezui, K. S.; Mlay, P. D.; Olojede, A. O.; Olowokere, F.; Busari, M.; Hauser, M.; Kreye, C.; Baijukya, F.; Merckx, R .; Pypers, P . (Elsevier, 2024)
Heterogeneity in soil fertility conditions impacts fertiliser use efficiency in smallholder cropping systems in sub-Saharan Africa. A study was performed to generate insights in nutrient limitations for cassava (Manihot esculenta Crantz.). We conducted 627 nutrient omission trials over three years in South East (SEN) and South West Nigeria (SWN), and in the Southern (TSZ) and Lake Zone of Tanzania (TLZ) to quantify variation in root yield responses to N, P and K, and relate these to digital soil maps and weather information. Mean fresh root yields were 30, 21, 13 and 15 Mg ha-1 with an application of 150–40-180 kg N-P-K ha-1 and 20, 16, 11 and 14 Mg ha-1 without nutrient addition in the four study areas, respectively. Root yield response to nutrients was largest in SEN, with mean root yield reductions of 5.7, 3.3 and 2.7 Mg ha-1 due to omission of N, P and K, respectively. Differences in yield and yield response to fertiliser between study areas were governed by rainfall conditions, which were most favourable in SEN, and least favourable in the TLZ. Within study areas, large spatial variation was observed, while temporal variation was limited. Spatial variation in yield response was largest in SEN with standard de-viations (sd) of 4.2 Mg ha-1 for K, 3.2 Mg ha-1 for P and 3.0 Mg ha-1 for N, opposite to the order of the mean yield responses. More than 75% of the variation in root yield response was observed at < 10 km scale, and close to 50% at < 1 km scale. Large variation (sd = 1.8 – 2.5 Mg ha-1) in response to N was also observed in all other study areas, and to K in SWN (sd = 2.4 Mg ha-1) and in the TSZ (sd = 2.1 Mg ha-1). Responses to N and P were weakly but significantly correlated to organic C, total N and clay contents, while response to K was correlated to extractable cations and clay content. Random forest models explained 16 – 59% of the variation in nutrient responses within study areas using digital soil maps and weather information. Our results confirm that responses to fertiliser nutrients vary in smallholder systems at a very local scale, and patterns vary between study areas and between individual nutrients. Digital soil maps and weather information can explain some of this variation and could support the development of site-specific recommendations at an appropriate scale. However, digital soil map data are unlikely sufficient to provide reliable advice at farm or plot level. Further research is needed to evaluate the capability of other factors, particularly local indicators of soil fertility, crop productivity and crop management intensity to complement digital soil maps in the development of field-specific fertiliser advice.